Animals on the move (İstanbul)
x, 270 sayfa
Keywords: “From the bustling streets of late Ottoman Istanbul to the vast pastures of Anatolia and the Balkans, Animals on the Move explores the intertwined lives of humans and livestock in a world undergoing profound transformation. Far from being silent resources, sheep, cows, and oxen shaped-and were shaped by-the forces of empire: state-building, capitalist expansion, urbanization, and environmental upheaval. Bringing together eight original studies, this volume shows how livestock sustained rural economies, trade networks, and urban industries while also bearing the brunt of displacement, disease, and disaster. By placing animals at the center of historical inquiry, Animals on the Move reveals how the destinies of humans and nonhumans alike were bound to the shifting dynamics of environment, economy, and empire in the Ottoman world” --